2015
DOI: 10.18632/oncotarget.5843
|View full text |Cite
|
Sign up to set email alerts
|

Silibinin-mediated metabolic reprogramming attenuates pancreatic cancer-induced cachexia and tumor growth

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is the fourth leading cause of cancer-related deaths in the US. Cancer-associated cachexia is present in up to 80% of PDAC patients and is associated with aggressive disease and poor prognosis. In the present studies we evaluated an anti-cancer natural product silibinin for its effectiveness in targeting pancreatic cancer aggressiveness and the cachectic properties of pancreatic cancer cells and tumors. Our results demonstrate that silibinin inhibits pancreatic cancer ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
68
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 77 publications
(70 citation statements)
references
References 53 publications
2
68
0
Order By: Relevance
“…Cell cycle analysis was performed by staining the cells with Telford reagent as described previously (22). Caspase 3/7 activity was determined by Promega Caspase-Glo kit (Madison, WI, USA) as described previously (23, 24). …”
Section: Methodsmentioning
confidence: 99%
“…Cell cycle analysis was performed by staining the cells with Telford reagent as described previously (22). Caspase 3/7 activity was determined by Promega Caspase-Glo kit (Madison, WI, USA) as described previously (23, 24). …”
Section: Methodsmentioning
confidence: 99%
“…RNA isolation and quantitative RT-PCR Total RNA was extracted from cells or tissue lysates by using TRIzol reagent (Invitrogen) as previously discussed (Shukla et al, 2015). cDNA was synthesized using Verso-cDNA synthesis kit (Thermo Fisher Scientific) according to the manufacturer's protocol.…”
Section: Cell Viability Assaysmentioning
confidence: 99%
“…Caspase 3/7 activity assay C2C12 myotubes were treated with control or cancer cell CM. Caspase 3/7 activity assay was performed using Promega Caspase Glo-kit as previously described (Shukla et al, 2015).…”
Section: Immunoblottingmentioning
confidence: 99%
“…Silibinin has been ascribed anticancer potential because of its manifold inhibitory effects on tumor growth in various cancer cells. Using cultured cells and animal models, Shukla et al showed that silibinin induces metabolic reprogramming, which diminishes the growth and cachectic properties of pancreatic cancer cells [31]. Momeny et al showed the potential anti-cancer activity of silibinin to inhibit the proliferative and invasive characteristics of the epithelial ovarian cancer cells that show an autocrine heregulin/human epidermal growth factor receptor 3 (HRG/HER3) pathway [32].…”
Section: Discussionmentioning
confidence: 99%